Respuesta :
5m-3h= 45
-5m -5m
(-3h= 45-5m)/(-3) to get h alone.
h= (-45/3)-(5/-3)m, simplify
h=-15+(5/3)m
-5m -5m
(-3h= 45-5m)/(-3) to get h alone.
h= (-45/3)-(5/-3)m, simplify
h=-15+(5/3)m
Answer:
h = [tex] -15 +\frac{5}{3}[/tex].
Step-by-step explanation:
Given : 5m − 3h = 45.
To find : Solve for h.
Solution : We have given 5m − 3h = 45.
On subtracting both sides by 5m.
- 3h = 45 - 5m.
On dividing both sides by -3 .
h = [tex]\frac{45 - 5m}{-3}[/tex].
h = [tex]\frac{45}{-3} +\frac{5}{3}[/tex].
h = [tex] -15 +\frac{5}{3}[/tex].
Therefore , h = [tex] -15 +\frac{5}{3}[/tex].